A review on DFACS (II): Modeling and analysis of disturbances and noises - YUE, Chenglei; JIAO, Bohan; DANG, Zhaohui; YUE, Xiaokui; ZHANG, Yonghe; XIA, Yuanqing; DUAN, Li; HU, Qinglei; LIU, Qifan; WANG, Pengcheng; GUO, Ming; DUAN, Zhansheng; et al. (Chinese journal of aeronautics, 2024)
•The sources of disturbances and modeling methods are provided.•The mechanism of noise generation in DFACS is analyzed.•Methods for integration, frequency domain analysis, and magnitude evaluation are summarized.•Reduction methods for interference factors and the challenges are pointed out.•Possible future research directions in this field have been presented. This paper presents Part II of a review on DFACS, which specifically focuses on the modeling and analysis of disturbances and noises in DFACSs. In Part I, the system composition and dynamics model of the DFACS were presented. In this paper, we discuss the effects of disturbance forces and noises on the system, and summarize various analysis and modeling methods for these interferences, including the integral method, frequency domain analysis method, and magnitude evaluation method. By analyzing the impact of disturbances and noises on the system, the paper also summarizes the system’s performance under slight interferences. Additionally, we highlight current research difficulties in the field of DFACS noise analysis. Overall, this paper provides valuable insights into the modeling and analysis of disturbances and noises in DFACSs, and identifies key areas for future research.